Study of the subjunctive mood in literary text using a Russian translation of Treasure Island - EMETS, T.; BARYSHNIKOVA, I.; TRUTNEV, A.; DROZDOVA, T.; MIKHAYLOV, V. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT This study aims to examine the methods by which the subjunctive mood is translated and to identify the most frequent forms in the original literary text and its Russian translations. This study involves a complex methodology, including the continuous sampling method, frequency analytic methods, a descriptive-analytical method, and linguistic analysis of English and Russian sentences. The material for the study included complex and simple subjunctive mood sentences extracted from the original English text of Treasure Island, by Robert Louis Stevenson, and its translation to Russian by Nikolai Korneevich Chukovsky. The results present and discuss features of the subjunctive mood. RESUMEN Este estudio tiene como objetivo examinar los métodos por los cuales se traduce el modo subjuntivo e identificar las formas más frecuentes en el texto literario original y sus traducciones al ruso. Este estudio involucra una metodología compleja que incluye el método de muestreo continuo, métodos analíticos de frecuencia, un método analítico descriptivo y análisis lingüístico de oraciones en inglés y ruso. El material para el estudio incluía oraciones de subjuntivo complejas y simples extraídas del texto original en inglés de Treasure Island, por Robert Louis Stevenson, y su traducción al ruso por Nikolai Korneevich Chukovsky. Los resultados presentan y discuten características del modo subjuntivo.